Hampiran Solusi Persamaan Gelombang Dua Dimensi Dengan Pendekatan Finite Difference - Syafii, Mohamad; Alghazali, Muhammad Rafli (JOSTECH: Journal of Science and Technology, 2022)
The finite difference method is widely used in determining the approximate solution of a time dependent partial differential equation. The purpose of this study is to calculate the numerical solution with a finite difference method to the two dimensional wave equation. The research method used is literature study. The solution of numerical problem using the finite difference method. Discretization the two-dimensional wave equation with a central difference approach. The second step, the discretization result isÂ  simulatedÂ  by Matlab software. Based on the finite difference method result, the numerical solution approximates the analytical solution of the given two dimensional wave equation. The stability requirements of numerical solution using the finite difference method is the Von Nuemann stability.